Effect of Forensic Accounting, Professional Skepticism, and Red Flags on Fraud Detection - Kusminarto, Zaskia Febrina Ananda; Amiruddin; Sundari, Sri (Pustaka Peradaban, 2026)
Financial statement fraud remains a critical challenge that can undermine public trust in the accounting and auditing professions. This study aims to examine and analyze the influence of forensic accounting, professional skepticism, and red flags on fraud detection. A quantitative approach was employed using primary data collected through questionnaires distributed to auditors at Public Accounting Firms (KAP) in Makassar, selected via purposive sampling. Hypotheses were tested using multiple linear regression analysis. The results indicate that forensic accounting, professional skepticism, and red flags have a positive and significant effect on the effectiveness of fraud detection. Theoretically, this research strengthens the synthesis of GONE Theory and Attribution Theory in explaining the fraud detection process within an investigative audit context. Practically, these findings provide a strategic reference for Public Accounting Firms in formulating auditor capacity-building strategies to be more systematic, critical, and evidence-based in detecting fraud. Kasus kecurangan laporan keuangan (financial statement fraud) tetap menjadi tantangan serius yang berpotensi mendegradasi kepercayaan publik terhadap profesi akuntan dan auditor. Penelitian ini bertujuan untuk menguji dan menganalisis pengaruh akuntansi forensik, skeptisisme profesional, dan red flag terhadap pendeteksian fraud. Penelitian ini menggunakan pendekatan kuantitatif dengan data primer yang diperoleh melalui penyebaran kuesioner kepada auditor pada Kantor Akuntan Publik (KAP) di Makassar. Teknik pengambilan sampel dilakukan dengan metode purposive sampling, sedangkan pengujian hipotesis menggunakan analisis regresi linear berganda. Hasil penelitian menunjukkan bahwa akuntansi forensik, skeptisisme profesional, dan red flag berpengaruh positif dan signifikan terhadap efektivitas pendeteksian fraud. Secara teoretis, penelitian ini memperkuat sintesis Teori GONE dan Teori Atribusi dalam menjelaskan mekanisme pendeteksian kecurangan pada konteks audit investigatif. Secara praktis, temuan ini memberikan rujukan strategis bagi KAP dalam mengoptimalkan kapasitas auditor agar lebih sistematis, kritis, dan berbasis bukti dalam mengidentifikasi indikasi kecurangan.